2021
DOI: 10.1021/acsnano.1c07772
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Successive Twinning Captured by Atomic Electron Tomography

Abstract: Shape-controlled synthesis of multiply twinned nanostructures is heavily emphasized in nanoscience, in large part due to the desire to control the size, shape, and terminating facets of metal nanoparticles for applications in catalysis. Direct control of the size and shape of solution-grown nanoparticles relies on an understanding of how synthetic parameters alter nanoparticle structures during synthesis. However, while outcome populations can be effectively studied with standard electron microscopy methods, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…The crystal planes of perovskite are main at 14.4° (1 1 0) and 28.8° (2 2 0). The diffraction intensities of perovskite main peaks increase and do not change position after lauric acid modification, demonstrating that the introduced lauric acid can passivate the defects and at the same time enhance the crystal growth quality of the perovskites without changing the crystal structure …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The crystal planes of perovskite are main at 14.4° (1 1 0) and 28.8° (2 2 0). The diffraction intensities of perovskite main peaks increase and do not change position after lauric acid modification, demonstrating that the introduced lauric acid can passivate the defects and at the same time enhance the crystal growth quality of the perovskites without changing the crystal structure …”
Section: Resultsmentioning
confidence: 96%
“…The diffraction intensities of perovskite main peaks increase and do not change position after lauric acid modification, demonstrating that the introduced lauric acid can passivate the defects and at the same time enhance the crystal growth quality of the perovskites without changing the crystal structure. 31 The FTIR spectra of pure lauric acid, pristine perovskite, and lauric acid-modified perovskite samples are shown in Figure 2b. Lauric acid has a strong peak of C�O stretching vibration at 1698 cm −1 , and the absorption peak moves to the low frequency of 1715 cm −1 in lauric acid-modified films, owing to the interaction between lauric acid and perovskite.…”
Section: Resultsmentioning
confidence: 99%
“…As a typical bimetallic nanocatalyst, Pt-Fe was studied at the early stage of nucleation, where the 3D reconstruction at atomic resolution revealed that the core of Pt-Fe particle was Pt-rich and remained unchanged, whereas a fraction of the surface and subsurface atoms were arranged to form L1 0 phase during annealing ( Figures 2R–U ). Similarly, Pelz et al applied AET to study the 3D atomistic structure of a multiply twinned Pd ( Pelz et al, 2022 ). Recently, Lee et al determined a full 3D atomic structure of a dumbbell-shaped Pt nanoparticle using deep learning assisted AET ( Lee, 2022 ).…”
Section: D Electron Tomography For Electrocatalysts At Atomic Scalementioning
confidence: 99%
“…Nanoparticles have drawn considerable attraction for their broad applications in many scientific fields including physics, chemistry, medicine, materials sciences, and others. Especially, metallic nanoparticles have shown great potential in the sense that their catalytic performance can be finely controlled based on growth conditions. Substantial efforts have been devoted to realizing their desired functional properties by controlling specific size, shape, and composition of the synthesized nanocrystals. Recent studies have revealed that the classical monomer attachment process is not the only mechanism for nanocrystal growth, and that particle–particle interaction, i.e., coalescence, also plays a crucial role in determining the size, shape, and structure of the nanocrystals. Therefore, the coalescence mechanism has been actively studied by theoretical calculations as well as in situ measurements, ,,,,,, and it has been shown that a coalescence event can result in not only single-crystalline nanoparticles, but also (multiply) twinned structures. ,,,, The twin or other grain boundary structures can be stably formed during the coalescence processes, introducing a substantial difference in the electronic structure at the surface. ,,, Since it can often be beneficial for catalytic performance, a better understanding of the coalescence and twinning process is important for fine tailoring of the nanocrystal structure and related catalytic properties. Furthermore, most of the oxygen reduction reaction (ORR) electrocatalytic activity measurements can only detect ensemble averaged properties, losing valuable information from individual nanoparticles. To manipulate the ORR activity at the atomic scale, it is required to fully map the 3D detail of local ORR properties from individual nanoparticles, which can be achieved by atomic-resolution 3D structural study.…”
mentioning
confidence: 99%